Current Understanding of piRNA in Cardiovascular Diseases - Cheang, Iokfai; Zhu, Qingqing; Liao, Shengen; Li, Xinli (Frontiers in Molecular Medicine, 2022)
The relationship regarding non-coding genomes and cardiovascular disease (CVD) has been explored in the past decade. As one of the leading causes of death, there remains a lack of sensitive and specific genomic biomarkers in the diagnosis and prognosis of CVD. Piwi-interacting RNA (piRNA) is a group of small non-coding RNA (ncRNA) which associated with Piwi proteins. There is an emerging strong body of evidence in support of a role for ncRNAs, including piRNAs, in pathogenesis and prognosis of CVD. This article reviews the current evidence for piRNA-regulated mechanisms in CVD, which could lead to the development of new therapeutic strategies for prevention and treatment.